Receptivity to Bariatric Surgery in Qualified Patients. (19th July 2016) - Fung, Michael; Wharton, Sean; Macpherson, Alison; Kuk, Jennifer L.
Abstract : Objectives . Bariatric surgery has been shown to be an effective intervention for weight loss and diabetes management. Despite this, many patients qualified for bariatric surgery are not interested in undergoing the procedure. The objective of this study is to determine the factors influencing receptivity to bariatric surgery among those who qualify for the procedure. Methods . Patients attending a publicly funded weight management clinic who qualified for bariatric surgery were asked to complete an elective questionnaire between February 2013 and April 2014. Results . A total of 371 patients (72% female) completed the questionnaire. Only 87 of 371 (23%) participants were interested in bariatric surgery. Individuals interested in bariatric surgery had a higher BMI (48.0 versus 46.2 kg/m 2, P = 0.03 ) and believed that they would lose more weight with surgery (51 versus 44 kg, P = 0.0069 ). Those who scored highly on past weight loss success and financial concerns were less likely to be interested in bariatric surgery, whereas those who scored highly on high receptivity to surgery and positive social support were more likely to be interested in bariatric surgery. Conclusion . Although participants overestimated the effect of bariatric surgery on weight loss, most were still not interested in bariatric surgery.